2019
DOI: 10.1021/acs.chemrev.8b00630
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Simulations of Membrane Ion Channel Conduction, Gating, and Modulation

Abstract: Membrane ion channels are the fundamental electrical components in the nervous system. Recent developments in X-ray crystallography and cryo-EM microscopy have revealed what these proteins look like in atomic detail but do not tell us how they function. Molecular dynamics simulations have progressed to the point that we can now simulate realistic molecular assemblies to produce quantitative calculations of the thermodynamic and kinetic quantities that control function. In this review, we summarize the state of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 916 publications
0
105
0
Order By: Relevance
“…While the precise ion-carboxylate LJ parameter will affect ion free energies within the ASIC pores, we have previously shown that selective binding is maintained regardless of the choice (Lynagh et al, 2017a). Modified LJ parameters, however, were used to describe the interactions between cations and carbonyl oxygen atoms of the protein to reproduce free energies of solvation in protein backbone mimetic, N -methyl-acetamide (Bernèche and Roux, 2001; Noskov et al, 2004; Allen et al, 2006; Flood, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…While the precise ion-carboxylate LJ parameter will affect ion free energies within the ASIC pores, we have previously shown that selective binding is maintained regardless of the choice (Lynagh et al, 2017a). Modified LJ parameters, however, were used to describe the interactions between cations and carbonyl oxygen atoms of the protein to reproduce free energies of solvation in protein backbone mimetic, N -methyl-acetamide (Bernèche and Roux, 2001; Noskov et al, 2004; Allen et al, 2006; Flood, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Permeating K + ions cannot occupy adjacent binding sites in the SF because of the electrostatic repulsion, and water molecules are intercalated between ions such that K + and water molecules (w) are aligned in alternating arrays, denoted as w-K + -w-K + and K + -w-K + -w. Morais-Cabral et al considered that the interconversion between the alternating arrays yielded rapid permeation. Molecular dynamics (MD) simulations reproduced the alternating arrays, and the simulation results were interpreted as an incoming ion that forced the expulsion of the downstream ion [17][18][19][20][21][22][23][24][25] via the three-ion-occupied intermediate (K + -w-K + -w-K + ; the "knock-on intermediate" [19]; Fig. 1, right lower snapshot) [15,16].…”
Section: Introductionmentioning
confidence: 96%
“…Over the last two decades, advances in X‐ray crystallography, and more recently in cryogenic electron microscopy (cryo‐EM), have provided atomic‐level ion channel structures to allow simulation studies of ion permeation, selectivity, gating and drug modulation . Each of these processes represents a challenge to simulation, because the time scales are either comparable to, or exceed that achievable with present day computers.…”
Section: Introductionmentioning
confidence: 99%